Digital 3d landskapsmodellering - Wadbro, John (2007)
In this paper I have sought a suitable level of abstraction in my models describing the landscape; the models are made to be viewed from eyelevel. Because of the spectator being "in the model" the objects included need a certain degree of realism. I have sought what is needed in the model to be able to comprehend that the model is showing a landscape. Some details might be unnecessary. My conclusions are: when viewing the landscape in the models from eyelevel, all errors appear instantly, but at the same time the things needed to experience the model as a landscape become clear. I choose to concentrate my modeling on the terrain; I created two models with differing resolution: one model created from points with 0.05 meters resolution and one model created from contour lines at 1meter intervals. During my research I came to the conclusion that only the model with the higher resolution (created from points with 0.05 meters resolution) could be used to represent the landscape. When viewed from another distance, the conclusion could be another one. The accuracy needed in the model is depending on in what purpose the models should be used. One other very interesting fact is that most people that viewed my models preferred the black and white renderings to the colour ones. The reason for the colour renderings being disliked, were minor colourerrors which appeared in the renderings, they where conceived as very annoying. These errors disappeared in the black and white renderings. I mean that similar colour errors can be seen in digital photographs as well, since some digital cameras have a tendency to oversaturate the colours, especially outdoors. It is impossible to copy nature, but it is possible to create an outdoor scene, in a computer, which can be useful to a landscape architect.